Social justice, decoloniality, and southern epistemologies within language education : theories, knowledges, and practices on TESOL from Brazil - Tavares, Vander, 1988- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"With a strong focus on decoloniality and social justice, this volume brings together critical theories, concepts, and practices on TESOL from multiple Brazilian perspectives. The chapters showcase the work of teachers and teacher educators in confronting sociopolitical issues in Brazil, including in the domains of democracy, language education, and knowledge production, as well as prevailing issues within TESOL itself. Contributions stem from an eclectic range of analytical orientations that reflect ontological and epistemological diversity while demonstrating why, where, and how TESOL is done in Brazil. In doing so, this volume also establishes a place for Southern voices to be heard in the move toward challenging complex and long-standing issues of representation, marginalisation, and exclusion that have traditionally characterised North-South relations in TESOL as a field. This volume seeks to promote Southern-based conversations about decoloniality and social justice in TESOL and will be of direct relevance to graduate students, researchers, and scholars in the field of TESOL and foreign language education"--
Includes bibliographical references and index.
ENH
Hye trade international
Keywords: English language -- Study and teaching -- Brazil; English language -- Study and teaching -- Social aspects; English language -- Study and teaching -- Political aspects; English language -- Study and teaching -- Portuguese speakers; Social justice and education -- Brazil; Essays